Pengaruh Pelatihan Dan Pengembangan Karir Terhadap Kinerja Karyawan Olive Fried Chicken Jalan Mayjen Sutoyo, Cacaban, Kota Magelang - Elyana Cindy Pratiwi; Bangun Putra Prasetya (CV. ITTC INDONESIA, 2024)
This research aims to analyze the influence of training and human resource development on the performance of PT. Raja Rasa Kuliner (Dkriuk Fried Chicken). The type of research used in this research is explanatory research or known as hypothesis testing to determine the effect of independent variables, namely Training (X1) and Development (X2) on the dependent variable Employee Performance (Y) using a quantitative approach. The sample used in this research was employees of Olive Fried Chicken), a total of 50 people. The sampling technique used was a purposive sample and 50 questionnaires collected which were used as primary data. The method used to collect data from respondents was a questionnaire with a Likert scale. Data analysis used multiple linear regression analysis processed with SPSS version 20 to determine the training and development of human resources for PT employees. Olive Fried Chicken). The independent variables in this research are training (X1) and development (X2), while the dependent variable is employee performance (Y). The results of this research are based on data analysis of hypothesis testing carried out, namely that the training (X1) and development (X2) variables simultaneously and partially have a significant effect on the employee performance variable (Y), apart from that the independent variable which has a dominant influence on the dependent variable is the development variable (X2).